Moisture Absorption and Thermal Expansion of Building Blocks Bound with Bitumen - Thanaya, I Nyoman Arya (Jurnal Teknik Sipil, 2009)
Abstract. This paper described about masonry wall building blocks that incorporate waste aggregate materials, namely steel slag, crushed glass, and coal fly ash. The binder used was 50 pen bitumen. The investigation was carried out at the University of Leeds United Kingdom (UK). The samples were produced by hot mixing the waste aggregates, compacting by static compaction, then applying heat curing to the compacted samples to harden the bitumen binder. The objective of the investigation was mainly to evaluate the building blocks compressive strength and volume stability (expansion and shrinkage) due to moisture and thermal exposure. It was found that the sampleâs compressive strength was comparable to concrete block commonly used in the UK. The volume stability of the sample was found largely irreversible due to moisture exposure, but highly reversible due to heat conditioning. The samples gave coefficient of thermal expansion comparable to clay bricks and concrete masonry blocks, and coefficient of moisture expansion similar to clay bricks. The blocks are suggested to be used for internal walls and are not exposed to outdoor weather, and should be protected with sand cement mix plaster.Abstrak. Paper ini menguraikan tentang blok pasangan dinding yang menggunakan agregat dari bahan bekas yaitu: steel slag, pecahan kaca, dan abu terbang batu bara. Bahan perekat yang dipergunakan adalah aspal penetrasi 50. Penelitian dilaksanakan di Leeds University United Kingdom (UK). Penggunaan bahan bekas dalam industri bangunan sudah digalakkan sejalan dengan strategi. Sampel diproduksi dengan dicampur secara panas, dipadatkan dengan pemadatan statis, dan dipanaskan untuk mengeraskan perekat aspal. Tujuan dari penelitian ini utamanya adalah untuk mengevaluasi kuat tekan dan stabilitas volume (pengembangan dan penyusutan) dari blok bahan dinding akibat terekspos air dan panas. Ditemukan bahwa kuat tekan sampel sebanding dengan jenis bata beton yang umum dipergunakan di Inggris. Stabilitas volume sampel dalam porsi besar tidak kembali ke kondisi semula akibat terekspos air, namun dapat kembali ke volume semula akibat terekspos panas. Sampel memberikan koefisien ekspansi termal yang sebanding dengan bata tanah liat dan bata beton, dan memberikan koefisien pengembangan lembab mirip seperti bata tanah liat. Blok pasangan yang diteliti ini, disarankan untuk digunakan sebagai dinding di dalam ruangan yang tidak terpapar cuaca luar dan diberi pelindung plesteran pasir-semen.